The Power of Green Intellectual Capital: Driving Sustainability and Profitability through ESG Practices - Sumiati, Sumiati; Isnaini, Araina (Jurnal Aplikasi Manajemen, 2024)
The pressing issue of climate change, driven by increasing greenhouse gas emissions, has made sustainable business practices critical for companies balancing profitability with environmental responsibility. This is particularly crucial in Indonesia, as the 8th largest greenhouse gas emitter globally with 1.3 gigatons of CO2e per year. This study explores the relationship between Green Intellectual Capital (GIC), sustainable performance, and profitability among companies listed on the Indonesia Stock Exchange. The research adopts a quantitative explanatory design, analyzing cross-sectional data from companies that disclosed their Environmental, Social, and Governance (ESG) scores. Using saturation sampling, all 121 companies from the population were included as the study sample, covering data from 2020 to 2022, resulting in 363 total observations. Path analysis was conducted using RStudio, incorporating comprehensive statistical tests including correlation, stationarity, multicollinearity, F-test, Hausman test, heteroscedasticity, and autocorrelation. The findings reveal that GIC does not significantly affect sustainable performance directly. However, the analysis reveals a strong link between sustainable performance and profitability, showing that companies engaging in sustainable practices see tangible financial benefits. Notably, while the GIC itself doesn’t have a straightforward impact on profits, its influence becomes significant when paired with sustainable performance. This study adds fresh insight by highlighting how GIC when aligned with environmental, social, and governance (ESG) standards, can indirectly boost profitability. These findings underscore the strategic value for businesses in merging GIC initiatives with holistic sustainability practices, aiming to enhance financial outcomes while also meeting environmental goals.